Comparison of biomechanical stability of osteosynthesis materials in long bone fractures - Predrag Grubor; Milorad Mitković; Milan Mitković; Milan Grubor (Medicinski glasnik, 2018)
Aim: To calculate stress and deformation under the force of pressure and bending in the dynamic compression plate (DCP), locking compression plate (LCP), selfdynamisable internal fixator (SIF) and locked intramedullary nail (LIN) in the models of juvidur, beef tibia bone (cadaver) and software of bone model simulator. Methods: Juvidur and bone models were used for the experimental study, static tests were performed with SHIMADZU AGS-X tester. CATIA software was used to create a 3D model for the SCA simulator, while software ANSYS to calculate the tension and deformation for compressive and bending forces. Stress and deformation analysis was performed with the use of Finite Element Analysis (FEA). Results: Weight coefficients of research methods were different (juvidur=0.3; cadaver=0.5; SCA Simuator=0.2), and weight coefficients of the force of pressure K p =0.5 and bending forces in one plane K 1 =0.25 and K 2 =0.25 in another plane, the overall result on the dilatation of DCP, LCP, LIN and SIF on juvidur and veal cadaver models showed that the first ranking was the LIN with a rank coefficient K U-LIN = 0.0603, followed by the IFM with K U-IFM = 0.0621, DCP with K U-DCP = 0.0826 and LCP with K U-LCP = 0.2264. Conclusion: Dilatation size did not exceed 0.2264 mm, hence the implants fulfilled biomechanical conditions for the internal stabilization of bone fractures. Prevalence goes to the locked intramedullar nailing and Mitković internal fixator in the treatment of diaphyseal, transversal, comminuted fractures in relation to DCP and LCP.
Keywords: osteosynthesis material; bone; software models; biomechanics